Linkability, Personhood and State Modernity: Understanding the Affordances of Personal Identity across Different Legal Regimes. Issue 2 (4th May 2019) - Hutton, Christopher
Abstract: "Linkability" is a technical term in data protection, referring to the ability of a third party to draw a connection between a person and a piece of data. The pattern of linkability may show that two apparently separate identities refer back to the same individual (e.g., a Twitter account and a Facebook account), or reveal a link a credit card and a travel pass, or a myriad of other linkages between data and individual identities. This article argues that linkability offers a more informative way of understanding legal personhood than traditional frameworks. Attempts to find a doctrinal grounding for personhood, for example, in privacy or self-ownership, fall into circularity. The "natural" versus "fictional" duality used to characterize the distinction between a person in being and a corporate person has given rise to fascinating but inconclusive ontological debates. It is suggested here that a relational understanding of the affordances that integrate personhood into a jurisdictional order reveals the underlying deep structure of legally constituted and recognized identities. The cases of the United States and India as common law jurisdictions and the People's Republic of China, a civil law jurisdiction with a Leninist understanding of the state, are analyzed.